Tahap Kemahiran Dan Kemudahan Penggunaan ICT: Satu Tinjauan Di Kalangan Pelajar-Pelajar KUIM - Rosidayu Sabran; Najwa Hayaati Mohd Alwi; Naim Hj Ahmad (Universiti Sains Islam Malaysia, 2024)
ICT education is one of the government's efforts in order to develop an informative and IT savvy society. Towards accomplishing government's vision in pursuing the development of communication and information technology in the country, attempts are made to impart ICT based teaching and learning in national education curriculum. The implementation is done through out every platform without considering on the background, education and ethnic. Therefore, this study is carried out to measure the Islamic University College of Malaysia's (KUIM) students which are from Islamic education background, on the ICT skills level. Moreover, this study also aims to measure that the ICT facilities in KUIM are in accordance to facilitate effective teaching and learning process. The result indicated that most KUIM students are knowledgeable in ICT. On the other hand the students have moderate level of ICT skills. In addition to that, the research result showed that the ICT facilities offered in KUIM are also moderate.